The application of Mississippi Protocol in superimposed pre-eclampsia patients with class 2 hemolysis, elevated liver enzymes, and low platelet count (HELLP) syndrome - Kusuma, Anak Agung Ngurah Jaya (Majalah Obstetri & Ginekologi, 2025)
HIGHLIGHTS The neonatal outcome following pregnancy termination was preterm birth, accompanied by low birth weight and respiratory distress. Following pregnancy termination, laboratory parameters gradually demonstrated improvement over time. Mississippi Protocol therapy was maintained for 4 days after pregnancy termination until both clinical status and laboratory values showed improvement.   ABSTRACT Objective: To describe the implementation of the Mississippi Protocol (MP) in a case of superimposed pre-eclampsia complicated by class 2 HELLP syndrome. Case Report: The patient initially received conservative treatment, including anticonvulsant prophylaxis, antihypertensive agents, and high-dose cortico-steroids, in accordance with the MP. However, during observation, placental abruption and fetal distress were noted. Consequently, an emergency (green code) Caesarean section was performed. Placental abruption is a known complication associated with pre-eclampsia. The neonatal outcome following pregnancy termination was premature birth, low birth weight, and respiratory distress. Following delivery, laboratory parameters gradually improved. MP therapy was continued for 4 days post-delivery until clinical and laboratory indicators normalized. The administration of high-dose corticosteroids in HELLP syndrome is based on its characteristic excessive inflammatory response, which represents the distinctive feature of this case. Corticosteroid therapy is intended to reduce maternal morbidity and mortality and to enhance neonatal outcomes. Conclusion: Careful monitoring and comprehensive management are essential when applying the MP in such cases. The definitive treatment for both pre-eclampsia and HELLP syndrome remains the termination of pregnancy. Further research is required to assess the effectiveness of MP in emergency or complicated scenarios.